Autonomous Fish Feeding Integrated System for Food Self-Sufficiency and Aquatourism Development in Malang City - Taufiqur Rokhman; Aeri Sujatmiko; Hj. Lis Setyowati; M Husen Hutagalung; Muhammad Ikhsan Setiawan; Che Zalina Zulkifli; Zulfiya Khabirova; Fazilat Kodirova (Malikussaleh University, Aceh, Indonesia, 2026)
This article examines the integration of autonomous fish-feeding systems with salt production and fish processing technologies as an innovative strategy to enhance food self-sufficiency, strengthen rural economies, and promote aquatourism development in Malang Regency, Indonesia. The region possesses significant potential in aquaculture, fisheries, and coastal resource utilization; however, productivity remains constrained by inefficient feeding practices, limited technological adoption, outdated processing methods, and infrastructure disparities. These challenges reduce production efficiency, increase operational costs, and limit the competitiveness of local fishery products in broader markets. The study employs a qualitative and participatory approach based on stakeholder engagement, field observations, focus group discussions, and technological gap analyses involving fish farmers, salt producers, tourism operators, local governments, and community organizations. The research develops an integrated innovation model that combines autonomous fish-feeding systems, smart aquaculture management, sustainable salt production, and value-added fish processing technologies within a unified economic ecosystem. The proposed model is designed to improve production efficiency while creating new tourism attractions centered on fisheries, coastal culture, and environmental education. The findings indicate that the adoption of automated feeding technologies can significantly reduce feed waste, lower operational costs, improve fish growth performance, and enhance overall aquaculture productivity. In addition, integrating fish processing and salt production activities with aquatourism creates diversified income sources, increases employment opportunities, and supports local entrepreneurship. The model also contributes to environmental sustainability by promoting efficient resource utilization and reducing production-related waste. The study concludes that the integration of autonomous aquaculture technologies with fisheries-based tourism represents not only a technological advancement but also a strategic pathway for economic transformation in coastal and rural regions. Furthermore, the proposed framework offers a scalable and replicable model for achieving sustainable food systems, community resilience, and inclusive regional development in Indonesia and other developing countries.